Bitcoin Financial Regulation: Securities, Derivatives, Prediction Markets, and Gambling - Brito, Jerry; Shadab, Houman B.; Castillo, Andrea (Science and Technology Law Review, 2014)
The next major wave of Bitcoin regulation will likely be aimed at financial instruments, including securities and derivatives, as well as prediction markets and even gambling. While there are many easily regulated intermediaries when it comes to traditional securities and derivatives, emerging bitcoin-denominated instruments rely much less on traditional intermediaries such as banks and securities exchanges. Additionally, the block chain technology that Bitcoin introduced for the first time makes completely decentralized markets and exchanges possible, thus eliminating the need for intermediaries in complex financial transactions. In this Article we survey the type of financial instruments and transactions that will most likely be of interest to regulators, including traditional securities and derivatives, new bitcoin-denominated instruments, and completely decentralized markets and exchanges. We find that Bitcoin derivatives would likely not be subject to the full scope of regulation under the Commodity Exchange Act to the extent that such derivatives involve physical delivery (as opposed to cash settlement) or are non-fungible and not independently traded. We also find that some laws, including those aimed at online gambling, do not contemplate a payment method like Bitcoin, thus placing many transactions in a legal gray area. Following the approach to virtual currencies taken by the Financial Crimes Enforcement Network, we argue that other financial regulators should consider exempting or excluding certain financial transactions denominated in Bitcoin from the full scope of their regulations, much like private securities offerings and forward contracts are treated. We also suggest that to the extent that regulation and enforcement becomes more costly than its benefits, policymakers should consider and pursue strategies consistent with that new reality, such as efforts to encourage resilience and adaptation by existing institutions.